Impact of genetic ancestry on the distribution of interferon-λ4 RS12979860 polymorphism in a global population of Buenos Aires, Argentina = Impacto de la ancestría genética en la distribución del polimorfismo de interferón-λ4 RS12979860 en una población global de Buenos Aires, Argentina - Mansilla, Florencia Celeste; Avena, Sergio; Dejean, Cristina; Turco, Cecilia Soledad; Capozzo, Alejandra (Sociedad Argentina de Genética, 2024)
Human interferon-λ4 is a cytokine involved in early stages of antiviral responses. Strikingly, some allelic variants with diminished antiviral activity reduce the susceptibility to viral infections, thus they would have suffered a positive selection pressure throughout the evolutionary history of the genus Homo. An intronic variant within the IFNλ4 locus (rs12979860, T˃C) emerged as one of the main gene determinants of the response to HCV and other viruses. The rs12979860-C allele has a differential frequency in African, European and Native American populations, though South American data are scarce. Here we characterize for the first time the distribution of rs12979860 genotypes in a sample of the global population of Buenos Aires, Argentina, assessing its association with European, Native American and African parental components. The rs12979860 genotypes were determined by PCR-RFLP in DNA samples from donors of a blood banks of Buenos Aires (n=96), whose genetic individual ancestry (European, African or Native American) had been previously determined using molecular markers. The distribution of rs12979860-CC, CT and TT was 29.17%, 50.0% and 20.83%, respectively. A significant increase in the frequency of CC among donors with a strong European contribution and a greater impact of the Native American component among donors carrying the T allele were observed. Native American and European components were associated to the rs12979860 distribution in a sample of the global population of Buenos Aires, while no differences were directly attributable to the African ancestry. Considering interferon´s key role in antiviral responses, our results may contribute to both bioanthropological and immunogenetic studies associated with infectious diseases.